Penerapan Model Pembelajaran Kooperatif Tipe Make A Math untuk Meningkatkan Hasil Belajar Siswa - Prihastini Oktasari Putri (Intersections, 2020)
This study aims to determine whether applying the Make A Math type of cooperative learning model can improve student learning outcomes in mathematics. The type of research used is Classroom Action Research. The sample in this study were all students of class VIIC SMP Negeri 7 Kebumen, totaling 24 students. The instruments used in this study were observation, documentation and tests Based on the results of the study, it was concluded that the application of the Make A Math type of cooperative learning model could improve student learning outcomes in mathematics class VIIC at SMP Negeri 7 Kebumen. The increase in student learning outcomes can be shown in the results of the final cycle test after applying the Make A Math type of cooperative learning model, the class average score was obtained with the results in the pre-cycle of 57.70; cycle I amounted to 67.08 and cycle II amounted to 78.95. With a percentage of completeness in the prasilkus of 33.33%, in the first cycle as many as 11 students completed with a percentage of 45.83% and in the second cycle there were 18 students who completed with a percentage of 75%